2022
DOI: 10.1021/acsaelm.2c00721
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on the Humidity Sensor: A Mini Review

Abstract: For the time being, a number of humidity measurement instruments made of a variety of different materials and operating on a number of different principles are accessible. There are numerous ways that may be utilized to categorize them. I begin by discussing the most commonly used designs for flexible humidity sensors. Following that, the section on humidity-sensitive materials, the sensing mechanism, the major properties of humidity sensors, and the influence of temperature on humidity sensors are discussed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 92 publications
(111 reference statements)
1
59
0
Order By: Relevance
“…In addition to the structures with the capacity for “proton jumps”, those with dielectric layers in between the electrodes usually act as capacitance-based humidity sensors. Generally, the formula used to link the capacitance output of the sensor and the varying dielectric constant of the sensing material in different wet environments is expressed as follows [ 34 ]: where C p is the sensor’s capacitance, ε 0 is the dielectric constant of the sensing material, ε r is the dielectric constant in air, S is the squared area of the capacitor poles, and d is the distance between the capacitor poles. At a given temperature, ε 0 is a definite value.…”
Section: Flexible Sensors For Sensing Humiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the structures with the capacity for “proton jumps”, those with dielectric layers in between the electrodes usually act as capacitance-based humidity sensors. Generally, the formula used to link the capacitance output of the sensor and the varying dielectric constant of the sensing material in different wet environments is expressed as follows [ 34 ]: where C p is the sensor’s capacitance, ε 0 is the dielectric constant of the sensing material, ε r is the dielectric constant in air, S is the squared area of the capacitor poles, and d is the distance between the capacitor poles. At a given temperature, ε 0 is a definite value.…”
Section: Flexible Sensors For Sensing Humiditymentioning
confidence: 99%
“…The design and sensing materials are the core components of humidity sensors. From the perspective of moisture-sensitive materials, materials with porous, pleated, and uniformly stacked structures often exhibit hydrophilic characteristics [ 34 ]. In addition to their structure, moisture-sensitive materials easily bind with water molecules because of their rich hydrophilic groups [ 42 ].…”
Section: Flexible Sensors For Sensing Humiditymentioning
confidence: 99%
“…According to [ 23 , 24 , 25 , 173 ], the ideal characteristics of a humidity-sensitive material are such properties as high sensitivity to water vapor, i.e., excellent affinity for water molecules and large active surface area, low cross sensitivity to other gases in the atmosphere, long service life, fast and reversible interaction with analytes, no long drift, efficient low cost technology, high reproducibility and good adhesion, i.e., uniform and strong bonding to the surface of the substrate. Experiment has shown that various types of sensing materials, including carbon materials and their derivatives (carbon nanotubes (CNTs), graphene oxide (GO), reduced graphene oxide (rGO)) [ 174 , 175 , 176 , 177 , 178 ], metal oxide semiconductors [ 179 , 180 ], organic materials [ 181 , 182 ], metal sulfides [ 183 ], and others [ 184 ], can be used for fabricating PB humidity sensors.…”
Section: Configuration Of Paper-based Humidity Sensors and Mechanisms...mentioning
confidence: 99%
“…6,7 Commercially available humidity-sensing technologies are diverse, ranging from units relying on monitoring capacitive, resistive, or thermal conductance changes occurring in material properties upon interaction with water vapor, to exploiting acoustic, optical or electromechanical effects. 6,[8][9][10] The versatility in chemical structure offered by organic compounds allows for synthetic designs that target specific interactions with water, and hence they quickly became popular in the humidity sensing arena, alongside active components in chemical and biological sensors. [11][12][13][14][15][16][17] Single-molecule-based sensors are particularly attractive since they can be integrated into semiconductor array chips to provide the much-sought electronics miniaturization.…”
Section: Introductionmentioning
confidence: 99%